Assessing social cognition and risk-taking behaviour in patients with young-onset dementia: Study protocol for the YOD-RiSoCo observational prospective cohort study - Floor Gelmers; Rients B. Huitema; Myrthe E. Scheenen; Barbara C. van Munster; Jacoba M. Spikman (PLoS ONE, 2025)
Background Certain subtypes of young onset dementia (YOD), such as the behavioural variant of FTD or the behavioural variant of AD (bvYOD), present with changes in social behaviour instead of memory impairments. These symptoms are often under-recognized, delaying the diagnosis and contributing to psychosocial problems. Impairments in social cognition (SC), an important affected domain in bvYOD, underlie these social behavioural changes. Especially emotional blunting and a lack of empathy in patients with bvYOD might be related to problematic social behaviour, such as risk-taking behaviour, which may potentially harm others. However, despite the importance of SC impairments in the diagnosis of YOD and the impact of SC impairments on social behaviour, there is a lack of valid and well normed measures for certain aspects of SC, such as emotion experience and empathy. Methods The YOD-RiSoCo study is an observational prospective cohort study, consisting of two separate, but related, studies. Study 1 includes 64 patients with bvYOD and 64 healthy controls to assess the sensitivity and validity of newly developed SC instruments for measuring emotion experience and empathy, by comparing their average group performance. Furthermore, validity of the new instruments will be assessed by analysing the associations of performances on these new tests with those on more traditional SC and other neurocognitive tests. Study 2 focuses on assessing to which extent SC measures relate to risk-taking behaviour. This study includes 20 patients with bvYOD and 20 healthy controls from Study 1, in addition to 20 patients with non-bvYOD (e.g. Alzheimer’s dementia or vascular dementia) and 20 patients with serious brain injury affecting frontal networks. A specific question is whether the relationship between SC and risk-taking behaviour is generic (for all groups with SC impairments), or specific (not in dementia without SC impairments). Discussion Results of the YOD-RiSoCo study will yield new, sensitive neuropsychological tests for aspect of social cognition, which may contribute to a more timely diagnosis of YOD, allowing earlier provision of appropriate counselling and care for patients and their close others. Furthermore, the study will contribute to a better identification of those social behavioural symptoms that negatively affect functioning and social relations. Trial registration The trial is registered at www.clinicaltrials.gov with identifier NCT06286293